(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What risks and challenges testing and calibration laboratories face when upgrading measuring equipment? Purpose: Investigate how Slovenian laboratories manage changes in the upgrade and/or replacement of their measuring equipment. Method: As a tool for obtaining the necessary information, we used a questionnaire developed for this purpose. In addition to descriptive and frequency statistics, we used Kruskal-Wallis tests to evaluate the data. Results: As the most frequently cited reason for the modernization of measuring equipment, they stated wear and tear, followed by an increase in capacity. The vast majority of investment in new measuring equipment was in line with expectations. We confirmed that most of the installations went correctly. The laboratories were more efficient after the change, and the new measuring equipment provides more reliable measurement results. To a smaller extent, the introduced changes were not successful. Considering the number of measuring systems, the number of persons dealing the laboratory equipment and the complexity, we did not prove statistically significant differences. Organization: Slovenian laboratories face the same challenges and manage risks as comparable foreign laboratories, which is an important message of the research. Society: Laboratories introduce constant changes and successfully manage them. This strengthens confidence in the reported results. These affect the quality and acceptability of various products and services, support industrial processes and are in the function of monitoring the environment. Originality: The results are directly useful and relevant in Slovenia and internationally. This is the first such research in Slovenia. Limitations / further research: We have limited to changes related to measuring equipment. Further research can be focused on a more in-depth analysis, focusing on different levels of management as well as other impacts, e.g. human resources. Laboratory responses could also be examined separately for transactional and transformational changes.